Staggered Contracts and the Frequency of Price Adjustment - Cecchetti, S. G. (Quarterly Journal of Economics, 1985)
This paper describes a methodology for measuring the frequency of price change in order to test the relevance of assuming prices to be set for discrete periods of time at overlapping intervals. Taylor [1980] has related the frequency of adjustment to the rigidity of the economy in responding to unanticipated events. Estimates of the frequency of price change are computed from data on the component parts of the deflator for personal consumption expenditure. The results show a substantial decrease in the period between price changes during the middle 1960s, and marked fluctuations in the 1970s. The movements suggest changes in the rigidity associated with both changes in general price inflation and changes in the posture of the fiscal and monetary authorities.